Analysis of 2222 colorectal polyps in 896 patients: A tertiary referreal hospital study - Solakoğlu, Tevfik; Atalay, Roni; Köseoğlu, Hüseyin; Özer Sarı, Sevil; Demirezer Bolat, Aylin; Akın, Ebru; Tayfur Yürekli, Öykü; Selvi, Eyüp; Büyükaşık, Şemnur; Ersoy, Osman (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: In Turkey, there are a limited number of studies including the characteristics of colorectal polyps, and the number of patients was too small in most of them. The aim of this study was to evaluate histological characteristics of colorectal polyps that were determined by colonoscopy and clinical features of patients who had removal of the polyp. Materials and Methods: Patients who underwent colonoscopy were analyzed retrospectively from January 2007 to December 2011. Adult patients (≥18 years) with no history of previous colorectal neoplasms who had removal of colorectal polyp were included. Results: A total of 2222 colorectal polyps were removed in 896 patients. Of these, 621 were male (69.3%) and 275 were female (30.7%). Most of the patients with polyps presented in the age group of 50-59 years (251 patients, 28%). It was recorded that 1816 (81.7%) of all polyps were adenomas. Of 1816 adenomas, 1577 (86.8%) were tubular adenomas. Of patients with adenomas, 19.7% was younger than 50 years. A total of 337 (37.6%) patients were in the high-risk group. Mean age of the high-risk patients was higher than the others (62±13 years and 58±13 years, respectively, p=0.001). Conclusion: This study is the largest series of colorectal polyps in Turkey to date. We determined the clinical and histologic characteristics of colorectal polyps and consider that the detection rate of colorectal adenomas in patients under the age of 50 years may be increased by the widespread use of colonoscopy as a diagnostic test.